2013
DOI: 10.1123/jsr.22.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Injury Occurrence: A Prospective Investigation of Professional Swedish Soccer Players

Abstract: The findings highlight the need for athletes, coaches, and medical practitioners to attempt to reduce state-level stressors, especially daily hassles, in minimizing injury risk. Educating and training athletes and coaches in proactive stress-management techniques appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 32 publications
7
119
1
12
Order By: Relevance
“…Clarsen and Bahr (2014), we chose to define PERFECTIONISM AND INJURY 9 injury specifically for the present study's context and population. As such, an athlete was defined as injured if the athlete required medical treatment and missed at least one training session or competition (see Ivarsson, Johnson, & Podlog, 2013). Of the 80 athletes, 38 experienced no injury, 24 one injury, 14 two injuries, and 4 three injuries over the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Clarsen and Bahr (2014), we chose to define PERFECTIONISM AND INJURY 9 injury specifically for the present study's context and population. As such, an athlete was defined as injured if the athlete required medical treatment and missed at least one training session or competition (see Ivarsson, Johnson, & Podlog, 2013). Of the 80 athletes, 38 experienced no injury, 24 one injury, 14 two injuries, and 4 three injuries over the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Another reason that caused participant's heart rate decrement during the trial could be due to their injuries started to recovering. Also, Ivarsson, Johnson, and Podlog [54] proposed five psychological predictors of injury occurrence (trait anxiety, negative-life-event stress, hassle, maladaptive coping, and injuries). In this study, participants who performed the imagery intervention had reported that lower anxiety level over the 12 weeks of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies has been identified where they have used the SSP instrument [8,30]. One study was performed on junior soccer players, where the aim was to develop psychological predictors in order to reduce injury risks among young soccer players [8].…”
Section: Discussionmentioning
confidence: 99%